Fine mapping and characterization of the Rous sarcoma virus Pr76gag late assembly domain. - Xiang, Y (1996)
The p2 region of the Rous sarcoma virus (RSV) Gag polyprotein contains an assembly domain, which is required late in replication for efficient budding of virus-like particles from cells (J. W. Wills, C. E. Cameron, C. B. Wilson, Y. Xiang, R. P. Bennett, and J. Leis, J. Virol. 68:6605-6618, 1994). This domain, referred to as the L domain, was previously mapped to the 11 amino acids of p2b. Through the analysis of a series of deletion and substitution mutations, the L domain has now been fine mapped to a highly conserved amino acid sequence, PPPPYV of p2b. Sequences flanking PPPPYV motif can be deleted without any effect on budding. Defects caused by L-domain deletions can be rescued by placing a wild-type copy of the sequence at several other positions in RSV Gag. A proline-rich P(S/T)APP motif is found in many retroviral Gag polyproteins; the motif found in the p6 region of human immunodeficiency virus type 1 has been implicated in late functions of the virus. Substitution of the RSV L domain with this motif in a 10-amino-acid sequence derived from visna leukemia virus results in wild-type release of virus particles from cells. In contrast, the slightly different sequences from Gibbon ape leukemia virus, Moloney leukemia virus, PSAPP alone, or a proline-rich SH3 binding sequence do not efficiently rescue RSV L-domain mutations.